Quality Characteristics of Rice-Based Ice Creams with Different Amylose Contents - Gi-Un Seong; Ji-Yoon Kim; Jung-Soo Kim; Sae-Ul Jeong; Jun-Hyeon Cho; Ji-Yoon Lee; Sais-Beul Lee; Nkulu-Rolly Kabange; Dong-Soo Park; Kwang-Deog Moon; Ju-Won Kang (Foods, 2023)
Ice cream consumption has increased over the years. In this study, we investigated the potential of using rice varieties with varying amylose contents for ice cream production. We analyzed the physical and chemical properties and sensory quality characteristics (appearance, taste, texture, chewiness, aroma, and rice flavor) of rice-based ice cream made from five varieties with low and high amylose levels. To make the ice cream, we ground rice into a fine powder and combined it with skim milk powder, butter, sugar, glycerin esters of fatty acids, locust bean gum, and water to form a gelatinized mixture. This mixture was then aged, frozen, and hardened. The ice cream’s key quality characteristics, such as viscosity (2170–25,030 cP), hardness (4.27–49.55 N cm−2), and overrun (17.95–46.99%), showed a wide range. Ice cream made from Saemimyeon (high amylose content rice variety) exhibited the highest hardness value (49.55 N cm−2) among the varieties tested, but had relatively low viscosity (4030 cP), overrun (17.95%), and drip-through (0.75 g/min) values. These findings suggest that rice varieties with different amylose contents are suitable for making ice cream and have the potential to expand the rice processing market and increase its value.